(untitled) (Huellas, 2022)
Since 2009, when Uribelarrea joined the "Tourist towns" program, it is possible to observe a series of changes as a consequence of the increase in activities related to rural tourism. This occurs in a context of revaluation of rural space, where they begin to be the object of consumption for city dwellers, who seek to satisfy needs associated with leisure and recreation. In this way, a touristification process begins in Uribelarrea, generating territorial adjustments to respond to the demands of visitors. This article is interested in analyzing those transformations linked to the process of building the attractiveness and promotion of this rural tourist destination, which recognizes two stages: (i) an initial stage, where this town begins to discover its "tourist vocation" and (ii) a more recent one, where it begins to consolidate with a more sophisticated profile.